Trust, Competition and Innovation: Theory and Evidence from German Car Manufacturers - Giacomo Calzolari; Leonardo Felli; Johannes Koenen; Giancarlo Spagnolo; Konrad O. Stahl (Center for Economic Studies and ifo Institute (CESifo), 2015)
We develop a simple theoretical model of a long term buyer-supplier relationship with non-contractible buyer specific R&D investment, and derive predictions on the effects of trust and competition on suppliers' investment and buyers' procurement strategies. We address these issues empirically using unique survey data on individual buyer-supplier relationships in the German automotive industry. Consistent with the model's predictions, higher levels of trust are associated with higher investment levels - but also with more competitive procurement: trust and rents from reduced supplier competition in the procurement process emerge as substitutes both in theory and in the data.
Keywords: D86; D22; L22; L62; 330; trust; hold-up problem; competition; innovation; specific investment; procurement; relational contracts; management practices; suppliers; car manufacturers; German automotive industry